2022
DOI: 10.1186/s12943-021-01492-7
|View full text |Cite
|
Sign up to set email alerts
|

Cancer exosomes and natural killer cells dysfunction: biological roles, clinical significance and implications for immunotherapy

Abstract: Tumor-derived exosomes (TDEs) play pivotal roles in several aspects of cancer biology. It is now evident that TDEs also favor tumor growth by negatively affecting anti-tumor immunity. As important sentinels of immune surveillance system, natural killer (NK) cells can recognize malignant cells very early and counteract the tumor development and metastasis without a need for additional activation. Based on this rationale, adoptive transfer of ex vivo expanded NK cells/NK cell lines, such as NK-92 cells, has attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 187 publications
(244 reference statements)
0
33
0
Order By: Relevance
“…It is believed that TGF-β1 exerts a significant inhibitory effect on NK cells. Specifically, TGF-β, existing as TGF-LAP in TDEs, can be activated by integrins and reduce NKG2D expression through the phosphorylation of SMAD with the intention of inhibiting NK cell activation and cytotoxicity [ 73 , 74 ]. Besides, exosomes from primary clear renal cell carcinoma cells are found to be preferentially rich in TGF-β1 [ 75 ].…”
Section: Immunosuppressive Role Of Tumor Cell-derived Exosomesmentioning
confidence: 99%
“…It is believed that TGF-β1 exerts a significant inhibitory effect on NK cells. Specifically, TGF-β, existing as TGF-LAP in TDEs, can be activated by integrins and reduce NKG2D expression through the phosphorylation of SMAD with the intention of inhibiting NK cell activation and cytotoxicity [ 73 , 74 ]. Besides, exosomes from primary clear renal cell carcinoma cells are found to be preferentially rich in TGF-β1 [ 75 ].…”
Section: Immunosuppressive Role Of Tumor Cell-derived Exosomesmentioning
confidence: 99%
“…For example, exosomes released from the synovial fibroblasts of patients with rheumatoid arthritis have high concentrations of membrane-bound TNF-α, which exacerbates the pathology of rheumatoid arthritis [ 85 ]. Human-cancer-cell-derived exosomes are also reported to have various immunosuppressive effects by suppressing interleukin 2 (IL)-dependent immune cell activation and causing the apoptosis of immune cells with NK activity by inducing cancer-specific cytotoxic T lymphocytes (CTL) through the amplification of regulatory T cells [ 86 , 87 ]. For example, when exosomes act on NK cells, they suppress the expression of the NKG2D receptor, which is responsible for the recognition mechanism of cancer cells and reduces cancer cytotoxicity [ 88 ].…”
Section: Regulation Of Immune Response By Exosomesmentioning
confidence: 99%
“…In addition, immature dendritic cell-derived exosomes (imDECs) can attenuate the inflammatory response and reduce the infiltration of CD4 + T cells [ 142 ]. Tumor-derived exosomes (TDEs) can inhibit the recruitment and migration of NK cells to the tumor environment, while suppressing the secretion of cytokines IFN-γ and TNF-α by NK cells, leading to immune escape and tumor progression [ 143 ]. Studies have revealed that MSCs-Exo can inhibit the proliferation of B cells and the differentiation into immunoglobulin-secreting plasma cells, and CCL2 in exosomes directly inhibits the secretion of immunoglobulin antibodies by plasma cells [ 144 ].…”
Section: Main Mechanisms Of Evs In the Treatment Of Oamentioning
confidence: 99%
“…EVs can be injected directly into the joint cavity in batches or combined with acellular scaffold materials to inhibit inflammatory factor release, and promote the polarization of M1 macrophages to M2 macrophages. Moreover, they also reduce the production of cartilage destruction factors, and promote the synthesis of factors involved in cartilage formation to immune escape and tumor progression [143]. Studies have revealed that MSCs-Exo can inhibit the proliferation of B cells and the differentiation into immunoglobulin-secreting plasma cells, and CCL2 in exosomes directly inhibits the secretion of immunoglobulin antibodies by plasma cells [144].…”
Section: Immunomodulationmentioning
confidence: 99%